Aspek Farmakologi dan Indikasi Corticosteroid - Gerry Setiawan; Ketut Suardamana (Cermin Dunia Kedokteran, 2023)
Corticosteroids have been widely used in various medical situations and often used for their anti-inflammatory and immunosuppressive effects. Corticosteroids can be given by many routes such as topical, oral, intramuscular, or intravenous. However, prolonged use of steroids can resultin hypothalamic-pituitary-adrenal axis suppression and other side effects. Dosage and using strategy are needed to get the best benefits while minimizing the risk of side effects